Analisis Penggunaan Bahasa Dalam Teks Pidato Siswa Kelas IX SMP Negeri 6 Pematang Siantar - Rugun Manalu; Jumaria Sirait; Junifer Siregar (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
This research aims to determine the analysis of language use in the speech texts of Class IX students at SMP Negeri 6 Pematang Siantar. The type of research used is qualitative research. The target of this research was class IX students at SMP Negeri 6 Pematang Siantar. The research location is at SMP Negeri 6 Pematang Siantar. Data collection techniques are observation techniques, documentation techniques, and interview techniques. The instrument in this research is a written test. The data in the research were analyzed using qualitative descriptive methods, namely the words obtained were interpreted by data reduction and data presentation. From the results of the analysis of speech texts with a total of 30 students in the aspect of spelling writing, 12 students writing punctuation, 21 students writing grammar, and 15 students writing vocabulary/terms. And the results of interviews conducted in research with 30 students at SMP Negeri 6 Pematang Siantar, there are still many students who have difficulty writing speech texts using standard language. There were 10 (33%) students who understood the use of standard language in writing speech texts, and there were 20 (67%) students who had difficulty in writing speech texts using standard language.